Pengembangan Majalah Fisika Pada Materi Usaha dan Energi Terintegrasi Islam - Rohmadi, Mukhlis; Septiana, Nurul (JIPFRI (Jurnal Inovasi Pendidikan Fisika dan Riset Ilmiah), 2023)
Reading is one of the most important efforts in the learning process. Student learning outcomes, especially business and energy materials, are still low due to the low interest in reading/student literacy, so media is needed that can increase students' reading interest. The purpose of this research is the development of learning media in the form of physics magazines that Islamic Integrated. The development of Islamic integrated magazine media is proceeds using the ADDIE development model. The results showed the results of material expert assessment with a percentage of 72.2% (feasible), media expert assessment with a percentage of 84% (feasible), and interpretation expert assessment with a percentage of 73.3% (feasible). In the trial, students obtained a good and positive response, by obtaining an average percentage of 79.54% with good and decent criteria. From the data from the expert assessment, the learning media for Islamic integrated physics magazines developed is declared feasible and can be used as a learning medium in Business and Energy materials.